CHANGES IN THE MAXIMUM OXYGEN CONSUMPTION IN KARATE ATH- LETES IN THE PREPARATORY AND PRE-COMPETITIVE PERIOD - Shkelzen Shalja,; Zorica Stankovska,; Zarko Kostovski,; Visar Ganiu, (Sport Scientific And Practical Aspects, 2025)
Karate training, as well as training in other martial arts, promotes positive adaptations to health-related physical fitness components. Among these components, maximum oxygen consumption (VO2max) is an important indicator of cardio- respiratory condition, as well as a strong and independent predictor of the risk of death from cardiovascular disease. Regular assessment of aerobic fitness is important to monitor the effectiveness of training processes and the willingness of karate fighters to compete. The need to determine the specific aerobic capacity of karate requires more specific tests and training protocols, so some studies have focused on physiological and temporal analysis of karate competitions. The aim of this study was to assess the level and differences of maximum oxygen consumption (VO2max) in karate athletes during training in the preparatory and pre-competition period, calculated using the (Beep t) test until dismissal. The research was conducted on a stratified sample of 16 male karate fighters, potential members of the national team from the Republic of Kosovo, in the period of preparations before participating in the World Cup for U21, juniors and cadets in Chile 2019. For each variable the basic descriptive statistical parameters were calculated separately: Arithmetic mean (Mean), standard deviation (SD), lower (min) and upper (max) result limit. One-Way Repeated-Measures ANOVA was used to determine the intergroup differences in the arithmetic means. To determine the special impact of each variable in creating group differences, the LSD test post hoc analysis was used